A meta-analysis of field-experiments using social norms to promote pro-environmental behaviors. (November 2019) - Bergquist, Magnus; Nilsson, Andreas; Schultz, Wesley P.
Highlights: We conducted a meta-analysis on field-experiments using social norms to encourage pro-environmental behaviors. Results of 91 field-experiments (N = 227′730) revealed a positive main effect of social norms on pro-environmental behaviors compared to no-treatment control conditions. Moderation analysis found that social norms induced implicitly were more influential than social norms induced explicitly and that social norms tended to be more influential in individualistic countries than in collectivistic countries.